Sun Exposure Shapes Functional Grouping of Fungi in Cryptoendolithic Antarctic Communities - Claudia Coleine; Laura Zucconi; Silvano Onofri; Nuttapon Pombubpa; Jason E. Stajich; Laura Selbmann (Life, 2018)
This is the final paper "Sun Exposure Shapes Functional Grouping of Fungi in Cryptoendolithic Antarctic Communities" published in Life 2018, 8, 19; doi:10.3390/life8020019 https://www.mdpi.com/2075-1729/8/2/19 Funded by the Italian National Program for Antarctic Researches (PNRA)